The Role Of The Principal In Encouraging The Improvement Of Teachers' Professional Competence At SMA Negeri 2 Muaro Jambi - Anggraini, Liza; Sudiono, Helik; Muspawi, Mohamad (Educational Leadership and Management Journal, 2024)
This study aims to describe the leadership of the principal in improving the professional competence of teachers at SMAN 2 Muaro Jambi and the efforts he must make. This research uses qualitative methods. The subjects are principals and teachers. Data collection techniques use observation, interviews and documentation studies. The results showed that the principal's efforts in improving teacher professional competence are facilitating teachers in carrying out self-development activities or improving their competencies, sending teachers to participate in competency improvement activities carried out outside of school and motivating and facilitating teachers to take part in Teacher Professional Education.